2014
DOI: 10.3389/fnhum.2014.00401
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological, Cognitive, and Emotional Mechanisms in Melodic Intonation Therapy

Abstract: Singing has been used in language rehabilitation for decades, yet controversy remains over its effectiveness and mechanisms of action. Melodic Intonation Therapy (MIT) is the most well-known singing-based therapy; however, speculation surrounds when and how it might improve outcomes in aphasia and other language disorders. While positive treatment effects have been variously attributed to different MIT components, including melody, rhythm, hand-tapping, and the choral nature of the singing, there is uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 105 publications
(154 reference statements)
0
40
0
3
Order By: Relevance
“…Further, we were unable to collect data on the size and location of the lesion of each participant as well as on the severity of their stroke. It has been suggested that these variables are related to MIT success (Lazar et al, 2008; Schlaug et al, 2008, 2009; Merrett et al, 2014). Hence, this information might have led to a better definition of MIT candidacy.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we were unable to collect data on the size and location of the lesion of each participant as well as on the severity of their stroke. It has been suggested that these variables are related to MIT success (Lazar et al, 2008; Schlaug et al, 2008, 2009; Merrett et al, 2014). Hence, this information might have led to a better definition of MIT candidacy.…”
Section: Discussionmentioning
confidence: 99%
“…21 For other approaches which have been practiced for decades, cognitive neuroscience helped to understand the mechanisms of action; this is the case for melodic intonation therapy, which seems to rely on the mirror neuron system and multimodal interactions, as well as on postlesional plasticity within the language and music systems. 22 Functional imaging in aphasic patients reveals changes in language organization, which is believed to underlie recovery and to reflect the effects of treatment. 23 After stroke in left hemispheric language areas, the noninjured language networks, which tend to be poorly activated in the acute stage, are transiently upregulated 2 weeks later, including the recruitment of additional regions in the right hemisphere.…”
Section: From the Wernicke-lichtheim-geschwind Model To Current Concementioning
confidence: 99%
“…Связь между слуховой и моторной корой, подчеркнутая в модели двойного потока, стала отправной точкой в терапии индуцированным ограничением при афазии [21]. Когнитивная нейробиология помогла понять механизм действия и других подходов, которые на протяжении десятилетий использовали в практике; например в случае мелодичной интонационной терапии, которая, по всей видимости, основана на активации зеркальной системы нейронов и мультимодальных взаимодействи-ях, а также на активации развивающихся после пов-реждения пластичности системы языка и музыкального восприятия [22]. Функциональная визуализация у пациентов с афазией демонстрирует изменения в организации речи, кото-рые, как полагают, лежат в основе восстановления и отражают эффективность терапии [23].…”
Section: Strokeunclassified
“…Musical and linguistic stimuli, such as chords and syllables, elicit distinct patterns of activation in the brain that tend to be right-lateralized for music and left-lateralized for language (e.g., Zatorre, Evans, Meyer, & Gjedde, 1992). Evidence for double dissociations of music and language processing comes from adults with congenital amusia, who have impaired pitch processing but perceive language normally (Peretz et al, 2002) and those with aphasia due to stroke, who have impaired language production but can nevertheless sing lyrics (see Merrett, Peretz, & Wilson, 2014).…”
Section: Introductionmentioning
confidence: 99%